Transparansi Dana Desa sebagai Faktor Penting dalam Mewujudkan Good Governance dan Akuntabilitas pada Kantor Pemerintah Desa Hilir, Kecamatan Balai, Kabupaten Sanggau - Nizam, Muhammad Nur; Rafa, Wukuf Dilvan; Karpriana, Angga p. (AKUNTANSI DEWANTARA, 2024)
In this study, transparency and accountability in the financial management of village funds are very important to achieve good governance. The focus of this research is on the role of government accounting in public financial management in the context of good governance. This research also examines the elements of transparency, accountability, and community participation in the management of village funds. The qualitative method applied uses semistructured interview techniques and the data used are primary and secondary data. The main findings of this study show that to increase public trust in the village government, transparency and community participation in the management of village funds are required. This research also discusses the principles of good governance that should be applied by village governments. These principles include accountability, transparency, efficiency, equality, rule of law, strategic vision, responsiveness, and consensus orientation. This research suggests increasing transparency, accountability, and community participation in the financial management of village funds to improve governance.